2021
DOI: 10.3390/app11219851
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrochemical Regeneration of Aqueous Amine Solutions to Capture CO2 and to Convert H2S into Hydrogen and Solid Sulfur

Abstract: Removing CO2 from natural gas or biogas in the presence of H2S is technically challenging and expensive as it often requires separation of both acid gases from the gas, typically using an aqueous amine solution, followed by separation of CO2 from H2S and conversion of H2S into solid S. In this work, the proof of concept of electrochemical, instead of thermal, regeneration of an aqueous amine solution is developed. This invention might be a very promising technology and has several advantages. It has H2S versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To simultaneously respect the asymmetrical H 2 S (<4 ppm) and CO 2 (<2.0–2.5 vol %) specification, a selective solvent can be used that preferentially absorbs H 2 S over CO 2. Techno-economic studies have shown that a further increase of the selectivity might lower the cost of CO 2 capture from natural gas containing H 2 S. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To simultaneously respect the asymmetrical H 2 S (<4 ppm) and CO 2 (<2.0–2.5 vol %) specification, a selective solvent can be used that preferentially absorbs H 2 S over CO 2. Techno-economic studies have shown that a further increase of the selectivity might lower the cost of CO 2 capture from natural gas containing H 2 S. , …”
Section: Introductionmentioning
confidence: 99%
“…Natural gas can contain significant amounts of acid gas (typically 0−30 vol % CO 2 , 0−30 vol % H 2 S), but the specifications of treated natural gas are very similar to biogas (around 4 ppm H 2 S and 50 ppm or 2.0−2.5 vol % CO 2 for LNG or pipeline, respectively) and can be reached with solely an amine scrubber, thanks to the high operating pressure of the absorption column. To simultaneously respect the asymmetrical H 2 S (<4 ppm) and CO 2 (<2.0−2.5 vol %) specification, a selective solvent can be used that preferentially absorbs H 2 S over CO 2. economic studies have shown that a further increase of the selectivity might lower the cost of CO 2 capture from natural gas containing H 2 S. 4,5 Low-pressure selective absorption is also applied in the natural gas industry, for example, in the acid gas enrichment (AGE) unit or the tail gas treatment unit (TGTU), in the upstream and downstream Claus sulfur recovery units, respectively. The main driving forces to improve the selectivity of the solvents in both TGTU and AGE are the reduction of CO 2 emissions, Claus unit optimization (only for AGE), and lower SO 2 emissions.…”
Section: ■ Introductionmentioning
confidence: 99%